Technology support and financing system for development and commercialisation-Perspectives in India - Sikka, Pawan
The technology support and financing system acts as a catalyst for stimulating economic growth through technology innovation, upgrading, adaptation and commercialisation in India. While describing all the relevant schemes available in the country, the author has critically assessed their role and has suggested a few remedial measures for their performance in the future so as to protect and provide a competitive edge to industry in excelling, at least in some fields, in the global market.
The technology support and financing system operating in India is investigated and assessed : some remedial measures are suggested to give a global competitive edge.
Keywords: Technology support; Financing system--India.